2013
DOI: 10.4103/0970-9185.105804
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal clonidine as an adjuvant to hyperbaric bupivacaine in patients undergoing inguinal herniorrhaphy: A randomized double-blinded study

Abstract: Background:Clonidine is added to intrathecal local anesthetics to improve intraoperative analgesia and to increase the duration of sensory and motor block. Aim of this study was to evaluate and compare the effects of addition of two different doses of clonidine (15 and 30 mcg) to 11 mg hyperbaric bupivacaine in patients undergoing inguinal herniorrhaphy surgery under spinal anesthesia.Materials and Methods:Seventy-five patients enrolled in the study were randomly divided into three groups of 25 each. Group I p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…[45] Several studies have shown that clonidine also has antihyperalgesic effect and thus reduces the post-operative analgesic requirement. [6]…”
Section: Introductionmentioning
confidence: 99%
“…[45] Several studies have shown that clonidine also has antihyperalgesic effect and thus reduces the post-operative analgesic requirement. [6]…”
Section: Introductionmentioning
confidence: 99%
“…Thakur et al in India reported that 15 μg and 30 μg of clonidine increased the time to regression of sensory block by the two dermatomes, sensory recovery in L3 and mean time to motor recovery; yet the 15 μg dosage was associated with less drop in mean systolic BP ( 11 ). Dobrydnjov in 2003 that 15 μg and 30 μg of clonidine were not significantly different in terms of duration of motor block ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clonidine has been assumed to have an inhibitory effect on afferent neurons in the posterior spinal horn, which may be due to the activation of noradrenergic descending pathways. Many studies have suggested administration of 15 - 75 µg, and 0.75, 1 and 2 µg/kg doses of clonidine with no serious complications in children and adults ( 7 - 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sensorial block levels of patients were evaluated with the “pin-pick” test applied in 5 min intervals. A Modified Bromage Scale 5 was used to evaluate the motor block.…”
Section: Methodsmentioning
confidence: 99%